(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the study and systematization of methods, ways and means of forming concepts in the process of teaching history. Also, to determine the role of historical concepts in the study of history, to highlight the features of the formation of concepts in the process of teaching history.